Assessment in distance education by confinement - Viramontes Anaya, Efrén; Viramontes Campos, Otoniel (IE Revista de Investigación Educativa de la REDIECH, 2021)
This document is a reflection, from the humanist perspective, on the evaluation of learning in a contingency situation, originated by the health emergency, which forced students throughout the Mexican educational system to be confined in their homes and to carry out school activities at a distance. It analyzes the problems in teaching and learning, in which evaluation plays an especially important role. It describes how, in the midst of uncertainty, institutions and teachers have carried out a series of actions to adapt evaluation to these conditions of improvisation and emerging decision making, most of which are intended to meet the needs of accrediting and certifying learning, as well as to compensate for the effects derived from confinement and the limitations to meet the demands of the educational system with the intention of saving school cycles. Along with the reflection and analysis, concrete actions are proposed that encourages the realization of a more adequate, fair, flexible, and inclusive evaluation.